PSYCHOLOGICAL ASPECTS OF THE MAIN CHARACTER IN OPPENHEIMER (2023) MOVIE - I Gusti Putra Kamayana; Komang Satria Wirasa (Universitas Duta Bangsa Surakarta, 2026)
The exploration of human psychological aspects is essential to understanding character development, particularly within cinematic narratives. Although previous psychological studies on film characters have extensively examined internal mental conflicts, they frequently overlook how these dimensions interact with broader narrative contexts, ethical dilemmas, and institutional power dynamics. To address this gap, this study aims to analyse the psychological aspects of the main character in Christopher Nolan's film Oppenheimer (2023) through the lens of Bernhardt's (1953) theory of human motivation. Employing a qualitative method with non-participant observation techniques, this research examines dialogues, scenes, non-verbal expressions, and actions based on five motivational classifications: appetites, wants, emotions, feelings and attitudes, and social motives. The analysis was validated through researcher triangulation during the data grouping and psychological interpretation stages. The findings reveal that while all classifications within Bernhardt’s framework are present, the emotional aspect emerges as the most dominant. This dominance directly reflects the intense inner conflict triggered by the moral pressure, scientific responsibility, and political power dynamics faced by the protagonist. In conclusion, these findings indicate that character development in films is profoundly driven by ongoing emotional struggles, thereby enriching literary and film psychology by integrating character analysis with complex historical and ethical contexts.